Reputation Based Trust Evaluation in E-Commerce Applications by Using Feedback Comments - Balaji, Penubaka; Nagaraju, O; Haritha, D (International Journal of Computer Sciences and Engineering, 2025)
Reputation and trust are two important key factors in e-commerce applications where as sellers or product ratings. In ecommerce applications, reputation is used to select best sellers among different available sellers by users. The reputation system models are used to project the different sellers based on their offering services and quality they provide to users. The trustworthiness of sellers are computed based on different models and method they opt in each model. Feedback comments of trust computation will be good impression as the users are free to direct themselves in free text feedback reviews. In proposed work we have calculating good reputation scores from users feedbacks based on a multidimensional trust model. In order to work this model, we have used algorithm for weights and ratings computation by mining feedback comments in which NLP, Topic Modelling techniques are used.